Pembelajaran Blended Learning Berbasis Whatsapp dalam Pelaksanaan Ekstrakurikuler Keagamaan Pada Masa Pandemi Covid-19 - Yulianto, Yulianto (Jurnal Didaktika Pendidikan Dasar, 2021)
Learning during the Covid-19 pandemic did not allow face-to-face implementation. The Ministry of Education and Culture issued circular number 4 of 2020 concerning home learning (belajar dari rumah/ BDR). The limitations that teachers have in mastering information technology are an obstacle in implementing bdr. lack of mobile phone facilities (gadgets) is another problem in implementing bdr. This obstacle is the main problem in implementing religious extracurricular activities. This problem is overcome by the application of WhatsApp-based blended learning. with the involvement of colleagues, the mastery of information technology for learning is increasing. teachers are not tech-savvy. Finally, the implementation of bdr in the implementation of religious extracurricular activities can run well.